Meningkatkan hasil belajar IPA dengan model pembelajaran kooperatif tipe jigsaw - Azizah, Umi (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this study was to improve the learning outcomes of science subjects in class VIII students of MTs N 6 Klaten using the Jigsaw Type Cooperative Learning model. This type of research is the Classroom Action Research (CAR) Model of Kemmis and Taggart which was conducted in 3 cycles. Each cycle was held 3 meetings consisting of planning, implementing, observing and reflecting. This research was conducted at MTs N 6 Klaten in the even semester of the 2017/2018 school year. The research subjects were 27 students of class VIII C. The research object is the result of science learning. The instrument for collecting data from the Observation and Test sheets was in the form of an essay. Data analysis using descriptive techniques. The results showed that the Jigsaw type learning model could improve the learning outcomes of class VIII students of MTs N 6 Klaten.